PENGARUH VARIASI DRILLS TERHADAP KETERAMPILAN SHORT PASSPADA PEMAIN SSB PUTRA KAPUR KECAMATAN KAPUR IX - Aroma Fauzi; Bafirman Bafirman (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The research problem was the lack of short pass skills of SSB Putra Kapur players in Kapur IX District. This study aims to determine the effect of variations in drills on short pass skills in SSB Putra Kapur players Kapur IX District.This type of research is quasi-experimental research. The population in this study were all players who were actively practicing at Putra Kapur SSB Kapur IX District, as many as 61 people. The sampling technique is purposive sampling technique, the sample of this study is 18 people. The instrument in this study used MC Donald Soccer Test to measure short pass skills. Data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t test) with a significance level α = 0.05.From the data analysis performed, the results obtained: There are effects of variations in drills with the ball on the reliability of the short pass SSB Putra Kapur players Kapur IX District, with the acquisition of the test coefficient